The China mission George Marshall's unfinished war, 1945/1947 - Kurtz-Phelan, Daniel (W. W. Norton & Company, 2018)
"A nuanced history of the doomed diplomatic mission that turned the tides of the Chinese Civil War. Following the phenomenal success of General George C. Marshall's leadership of the American army during World War II, he was the standout candidate for a vital international mission: brokering a coalition government between China's warring Nationalists and Communists. Marshall went overseas as a U.S. "special representative" and began enacting miraculous change. Under Marshall's guiding hand, China's embattled political factions agreed to a ceasefire and settled on the principles of a democratic government. But over the next ten months, Marshall's mission soured: the agreements he brokered fractured and civil war came to China after all. This fascinating narrative history portrays the incredible beginnings and ultimate failure of Marshall's high-stakes mission, with a remarkable cast of characters featuring a heroes' gallery of American diplomats...Truman, Eisenhower, MacArthur, and many others. In spellbinding, pinpoint detail, The China Mission chronicles an unforgettable misstep in American diplomacy that changed the course of global politics forevermore."...Provided by publisher